A history of West Africa - Falola, Toyin, author.
1 online resource (xiv, 512 pages)
Keywords: "This book introduces readers to the rich and fascinating history of West Africa, stretching all the way back to the stone age, and right up to the modern day. Over the course of twenty seven short and engaging chapters, the book delves into the social, cultural, economic and political history of West Africa, through prehistory, revolutions, ancient empires, thriving trade networks, religious traditions, and then the devastating impact of the Trans-Atlantic slave trade and subsequent colonial rule. The book reflects on the struggle for independence and investigates how politics and economics developed in the post-colonial period. By the end of the book, readers will have a detailed understanding of the fascinating and diverse range of cultures to be found in West Africa, and of how the region relates to the rest of the world. Drawing on decades of teaching and research experience, this book will serve as an excellent textbook for entry-level History and African Studies courses, as well as providing a perfect general introduction to anyone interested in finding out about West Africa"--